"Band Wagon and Gravy Train": uses and abuses along the Silk Road. Issue 2 (October 2019) - Ball, Warwick
Abstract : The Silk Road as an image is a relatively new one for Afghanistan. It appeals to both the pre-Islamic and the perceived Islamic past, thus offering an Islamic balance to previous identities linked to Bamiyan or to the Kushans. It also appeals to a broader and more international image, one that has been taken up by many other countries. This paper traces the rise of the image of the Silk Road and its use as a metaphor for ancient trade to encompass all contacts throughout Eurasia, prehistoric, ancient and modern, but also how the image has been adopted and expanded into many other areas: politics, tourism and academia. It is argued here that the origin and popularity of the term lies in late 20th century (and increasingly 21st century) politics rather than any reality of ancient trade. Its consequent validity as a metaphor in academic discussion is questioned